THE PROBLEM OF DIFFERENTIATION OF REGULATED AND SELF-REGULATED LEARNING WITHIN THE CONTEXT OF LEARNING ACTIVITY - Yana Koryakina (Вестник Северо-Кавказского федерального университета)
This article is devoted to the problem of comparative study of two educative processes, their structural and conceptual components. The article depicts the range of consecutive and interrelated actions, the difference of their resources within the context of implementing their individual characteristics that encourage the development of the autonomous learner able to perform the process of learning in a more independent way in the context of formal education. Today we can speak about new education technologies that emphasize the individual learner's skills, value orientation and educational content. The analysis made on the problem of comparison of directed and self-directed learning let us to set aims which are urgent in socio-cultural environment in a current informative society.